User provided network system with incentive mechanism [Teşvik Mekanizmali Kullanici Saǧlayicili Aǧ Sistemi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
The increasing mobile data requirement on mobile devices has led to the concept of User Provider Network (UPN), which is based on sharing the users' Internet connections. According to this approach, users with cellular connection share their own connections with others with limited or no cellular connection. The basic research problem in the UPNs is mostly about incentivizing users to participate in the system. Proposed incentive mechanisms are usually not based on realistic parameters in terms of cost and utility modeling. In this work, our goal is to develop a realistic cost and utility modeling method for operator controlled UPN services and to design a UPN system with an incentive mechanism using the developed method. © 2017 IEEE.
Keywords: bargaining; LTE; power modeling; User provided networks; utility/cost modeling